Energy efficient strategies for the building envelope of residential tall buildings in Saudi Arabia - Ghabra, Noura (2018)
The energy demand in the oil- dependent Gulf countries in general and in Saudi Arabia in particular has been increasing sharply in the last decades as a result of the diversification plans. Tall building construction, associated with many environmental and ecological challenges, played an essential role in these plans, as a mean to attract new economies based on global placemaking and international tourism. The significant use of air conditioning to cool indoor spaces, particularly in residential buildings, accounts for more than half of all energy consumption in the country, and despite governmental efforts, the scattered conservation efforts have been largely ineffective due to factors such as lack of awareness and information, in addition to the limitation of the local energy efficiency building regulations. This research aimed to find and prioritise building envelope design solutions that can reduce high energy consumption and cooling loads while maintaining indoor environment for residential tall buildings in Saudi Arabia. In order to achieve that, a hypothesis of integrating the thermal properties and design parameters of the building envelope as a design strategy for tall buildings envelope were proposed, and to test it, a mixed method approach was followed including literature review, data collection, dynamic building simulations and parametric analysis. The main findings emphasised how combining both the thermal properties and design parameters of the building envelope can be an effective way to achieve energy efficiency in residential tall buildings in the hot climate of Jeddah. Especially in relation to solar heat gains, the highest contributor to cooling loads in this building type. The findings highlighted that while the thermal properties of the wall type can reduce up to 10% of the cooling loads, applying external shading devices can achieve a reduction of up to 30% in solar gains. Moreover, effective consideration of building orientation can significantly reduce cooling loads by 25% and solar gains by 60% for the perimeter zones. Based on this, a set of guidelines that incorporate a comparative tool were introduced to help designers to determine the thermal performance and energy use of a typical residential tall building in the early stages of the building’s design. Which also aim to enhance the effectiveness of the local building codes and energy efficiency regulations in relation to this building type.